Bahan Ajar Bangun Datar Berbasis Masalah di Kelas V SD - Rangkuti, Muhammad Zhaky; Sukmawarti, Sukmawarti (LPPM UMN Al Washliyah, 2024)
This development research aims to develop problem-based flat shape teaching materials that are suitable for use in the learning process in 5th grader. This research is development research using the ADDIE development procedure which consists of 5 stages. In this research, researchers implemented the ADDIE development model only up to the development stage. The instrument used to collect data was a questionnaire given to several expert validators, namely media expert validators, material expert validators and learning expert validators. From the material expert validation results, a score of 85 was obtained with the criteria